In praise of tax havens: international tax planning and foreign direct investment - Qing Hong; Michael Smart (Center for Economic Studies and ifo Institute (CESifo), 2007)
The multinationalization of corporate investment in recent years has given rise to a number of international tax avoidance schemes that may be eroding tax revenues in industrialized countries, but which may also reduce tax burdens on mobile capital and so facilitate investment. Both the welfare effects of and the optimal response to international tax planning are therefore ambiguous. Evaluating these factors in a simple general equilibrium model, we find that citizens of high-tax countries benefit from (some) tax planning. Paradoxically, if tax rates are not too high, an increase in tax planning activity causes a rise in optimal corporate tax rates, and a decline in multinational investment. Thus fears of a race to the bottom in corporate tax rates may be misplaced.
Keywords: H2; H7; 330; income shifting; tax planning; foreign direct investment; tax competition; thin capitalization; Unternehmensbesteuerung; Multinationales Unternehmen; Steuerplanung; International; Direktinvestition; Steuerwettbewerb; Optimale Besteuerung; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie